PEMANFAATAN DEVISA PEKERJA MIGRAN INTERNASIONAL DI NUSA TENGGARA BARAT - Lalu Tajuddin; Tukiran Tukiran (Populasi, 2006)
West Nusa Tenggara is wellknown as the sending place for international migrant workers, especially to Saudi Arabian and Malaysia. The foreign exchanged they produced is big enough, almost Rp1,6 millions per day. Unfortunately, the local government did not receive anything from that amount, except for many complicated problems occurs by the international migrant workers. Many brokers or fund supported agents had benefit from the workers by preparing their administration paper for the departure. These people also put higher interest on the loan made by the workers and they have a lot of money considered that each year the amount of international migrant workers have increased. On the other side, the local government still resistant in showing goodwill to become the fund supported agent which can protect the workers from loan with higher interest.